PROSPECTIVE OBSERVATIONAL STUDY ON THE IMPACT OF ULTRASONOGRAPHY ON PREGNANCY OUTCOMES IN CASES OF THREATENED ABORTION, CHENNAI: A CROSS-SECTIONAL STUDY. - Selvam, Vidhya; Lakshmi. P, Mohana; Kalaivani (Student’s Journal of Health Research Africa, 2024)
Background Threatened abortion, recognised by vaginal bleeding during the first 20 weeks of pregnancy, can result in unfavourable consequences such as intrauterine growth restriction, preterm birth, and miscarriage. Ultrasonography is essential for monitoring these pregnancies and predicting outcomes. The study aims to examine the predictive value of bleeding patterns and ultrasound findings on pregnancy results in females with threatened abortion. Methods The study comprised 100 pregnant women with threatened abortion. Bleeding patterns were categorized as light or heavy. Key ultrasound findings were recorded. Pregnancy outcomes, including loss before 20-weeks’ gestation and late complications, were assessed. Statistical analyses, including chi-square tests and logistic regression, were employed to assess associations between variables and outcomes. Results The average age was 28.4 years (± 4.2), and the average BMI was 22.3 kg/m² (± 1.8). The average gestational age was 8 weeks (± 1). On average, participants had 1.5 previous pregnancies. Among them, 40% were primigravida and 60% were multigravida. Pregnancy loss before 20-weeks’ gestation occurred in 25 participants (25%), while 35 participants (35%) experienced late pregnancy complications. Heavy bleeding was significantly associated with pregnancy loss (OR = 2.8, 95% CI [1.3, 6.0], p = 0.008). Subchorionic hematoma (OR = 2.1, 95% CI [1.0, 4.3], p = 0.045) and cervical length less than 2.5 cm (OR = 3.0, 95% CI [1.2, 7.2], p = 0.018) were also significant predictors of early pregnancy loss. Conclusion Heavy bleeding, subchorionic hematoma, and shortened cervical length are significant predictors of loss of pregnancy prior 20-weeks’ gestation in women with threatened abortion. The findings underscore the importance of close monitoring and comprehensive care for at-risk pregnancies. Recommendations Further research is needed to develop targeted interventions for pregnancies with threatened abortion. Clinicians should use ultrasound findings and bleeding patterns to guide the management and counseling of affected patients.